Umbilical hernia strangulated to liver contents - Piñeyro, Alberto; Perrier, José; Bergalli, Luis (Cirugía del Uruguay, 1978)
Report on a rare clinical case in which Segment III of liver was contained in a strangulated umbilical hernia. This required atypical resection for its better treatment.